The Art of Critical Thinking in Studying Philosophy - Nala Sri Ayu Luthfiah; Balqis Tsaniyah Azzahra; Didik Himmawan (Annujum: Journal of Humaniora and Law, 2025)
Philosophy has a key role in the intellectual development of human beings. Philosophy not only teaches us to ask questions deeply, challenge balanced beliefs, and formulate complex thoughts, but it also develops the ability to think systematically and analytically about complex ideas, arguments, and concepts. The purpose of this research is to find out the concept of critical thinking and the benefits in studying philosophy. The research method we use is a qualitative method using library research, library research, which is a method with data collection by understanding and studying theories from various literature related to the research. The type of research is literature research or library research. The result of this research is that the art of critical thinking in philosophy is not only about understanding complex concepts, but also about developing critical, analytical, and reflective thinking skills. This is the basis for sustainable personal growth and meaningful contributions to society at large.